Gambaran Jumlah dan Hitung Jenis Leukosit Ayam Petelur yang diinfeksi L2 Toxocara Cati - Diyah Ayu Candra; Nunuk Dyah Retno Lastuti; Nove Hidayati; Kusnoto Kusnoto; Poedji Hastutiek; Retno Bijanti (Journal of Parasite Science (JoPS), 2020)
The aim of this study was to determine leukocytes and differential counting in chicken after infected with L2 Toxocra cati. In this study, it was used twenty chickens, wich were 14 weeks old. They were divided into 4 groups. Chickens were infected by orally with dose 0 eggs/ml L2 T. cati, 10 eggs/ml L2 T. cati, 100 eggs/ml L2 T. cati and 1000 eggs/ml L2 T. cati. Blood sampling were conducted on 2, 7 and 21 days after infection. Leukocyte value was determined by improve neubauer and differential counting stained with Wright’s stain then determined using microscope 1000x. The data was analyzed by Anova Factorial and then continued by BNJ Test at 5%. The result showed that increased of leukocytes value and eosinophil at 7 and 21 days after infection L2 T. cati with different dose, increased of leukocytes value and eosinophil on infection dose 10 eggs/ml L2 T. cati, 100 eggs/ml L2 T. cati and 1000 eggs/ml L2 T. cati. It shows that there was not intereraction between time of infection process and infection dose of L2 T. Cati.